NILAI-NILAI PENDIDIKAN KARAKTER DALAM KISAH UMAR BIN KHATTAB SEBAGAI KHALIFAH - Papat Siti Patimah; Fauzan Fauzan; Hayati Hayati; Alimir Alimir (Universitas Pahlawan Tuanku Tambusai, 2022)
Umar bin Khattab was one of the companions of the Prophet who had extraordinary character and personality. Allah SWT has honored Umar bin Khattab with Islam which gave him a true and pure faith. Umar walked on the manhaj of the Prophet Muhammad and received education directly from the Prophet Muhammad. So that Umar bin Khattab gave an example of noble character and character, especially after he converted to Islam and served as Caliph. He shows how the character and morals that a real leader must have and provides an example to his people. In this study, the author uses a type of library research, namely deepening, reviewing and identifying existing knowledge in the literature (reading sources, reference books or other research results). The data sources in this study are: primary sources and secondary sources. While the research method uses descriptive analytical methods, namely efforts that are focused on problems that exist in the present by collecting data that exist in the present and then analyzed. The values of character education that the authors can conclude in this study are thirteen, namely: Religious, Honest, Tolerant, Disciplined, Hard Work, Creative, Independent, Democratic, Appreciating Achievement, Friendly / Communicative, Peaceful Love, Social Care and Responsibility . Keywords: Character building, educational value, umar bin khattab